A Comprehensive Study on Pathfinding Techniques for Robotics and Video Games. (2nd April 2015) - Abd Algfoor, Zeyad; Sunar, Mohd Shahrizal; Kolivand, Hoshang
Abstract : This survey provides an overview of popular pathfinding algorithms and techniques based on graph generation problems. We focus on recent developments and improvements in existing techniques and examine their impact on robotics and the video games industry. We have categorized pathfinding algorithms based on a 2D/3D environment search. The aim of this paper is to provide researchers with a thorough background on the progress made in the last 10 years in this field, summarize the principal techniques, and describe their results. We also give our expectations for future trends in this field and discuss the possibility of using pathfinding techniques in more extensive areas.